KONSEP SULUK ZAINUDDIN AL-MALIBARI: Jalan Tritunggal Menuju Ma’rifat Allāh (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
Discussions on "suluk" have been extensively covered by scholars and experts in the field of Sufism. However, it becomes particularly intriguing when "suluk" is examined by scholars known for their expertise in Islamic jurisprudence or fiqh, like Zainuddin al-Malibari. In several Sufi literary works, "suluk" places greater emphasis on the process, spiritual activities, or practices aimed at reaching Allah SWT. Consequently, its practical application often encounters errors due to misinformation. In his book "Hidāyat al-Adhkiyā’", Zainuddin al-Malibari delves into the misunderstandings faced by individuals undertaking "suluk". This research aims to document a concept of "suluk" within the treasury of Sufism from the perspective of a fiqh expert. It also aims to address the deficiencies in previous research articles. This study employs a library research approach, where collected data comprises both primary (main) and secondary (supporting) sources. Zainuddin al-Malibari's book "Hidāyat al-Adhkiyā’" serves as the primary data source, while secondary sources include books, journals, and various internet resources discussing Zainuddin al-Malibari's thoughts. The research findings highlight that Zainuddin al-Malibari's concept of "suluk" encompasses three components: Sharia, Ṭariqat, and Ḥaqiqat. To attain ma’rifat Allāh, an individual undertaking a spiritual journey (salik) must firmly abide by Sharia initially. Even upon reaching the stage of understanding the Ḥaqiqat, Sharia remains a responsibility to be upheldPembahasan mengenai suluk banyak ditulis oleh ulama atau sarjana di bidang tasawuf. Tetapi menjadi menarik apabila suluk dibahas oleh ulama dan sarjana yang dikenal sebagai ahli fikih atau ahli yurisprudensi Islam, Zainuddin al-Malibari. Dalam beberapa literatur tasawuf, suluk lebih menekankan proses atau kegiatan spiritual atau praktik menuju Allah Swt. Sehingga tidak jarang dalam penerapannya terdapat kekeliruan yang disebabkan mis-informasi. Dalam kitab Hidāyat al-Adhkiyā’, Zainiddin al-Malibari menjelaskan tentang kesalahpahaman seseorang yang menempuh suluk. Penelitian ini ingin mendokumentasikan suatu konsep suluk dalam khazanah tasawuf menurut pandangan ahli fikih. Serta melengkapi kekurangan dari artikel penelitian yang ada sebelumnya. Jenis penelitian pustaka (library research) merupakan penelitian yang dipakai pada penelitian ini. Umumnya, pada penelitian kepustakaan (library research) ini, sumber data yang dihimpun dalam melengkapi penelitian ini terdiri dari data primer (pokok) dan data sekunder (penunjang). Kitab Hidāyat al-Adhkiyā’ Zainuddin al-Malibari adalah sumber data primer. Sedangkan sumber data sekundernya berupa buku, jurnal dan beberapa sumber dari internet yang memuat pemikiran Zainuddin al-Malibari. Hasil dari penelitian ini bahwa konsep suluk Zainuddin al-Malibari melalui tiga bagian: Syariat, Tarekat, dan Hakikat. Agar sampai kepada ma’rifat Allāh, seorang yang melakukan pengembaraan spiritual (salik) harus kokoh dalam menjalankan syariat terlebih dahulu dan meskipun nantinya sudah sampai pada bagian hakikat, syariat masih tetap menjadi tanggung jawab untuk dijalankan.